Identification of hot spots and co-occurrence patterns of activities on thyroid hormone receptor and transthyretin binding in passive samplers from Czech surface waters - Šauer, Pavel; Bořík, Adam; Staňová, Andrea Vojs; Grabic, Roman; Kodeš, Vít; Amankwah, Beatrice Kyei; Kocour Kroupová, Hana (Environmental research, 2024)
One of the less studied in vitro biological activities in the aquatic environment are thyroid hormone receptor beta (TRβ)-mediated agonistic and antagonistic activities and transthyretin (TTR) binding activity. They were measured mostly using active sampling methods, but rarely found. It is unclear if these activities co-occur, and the drivers of the (anti-)TRβ activity are mostly unknown. Therefore, the main aim of the study was to determine (anti-)TRβ activities as well as transthyretin (TTR) binding activity in passive samplers from Czech surface waters in combination with the search for the effect drivers based on liquid chromatography-high resolution mass spectrometry (LC-HRMS) analysis by applying suspect screening. Passive samplers (polar organic chemical integrative samplers, POCIS) were deployed at twenty-one sites (all ends of watersheds and other important sites in Elbe River) in the Czech rivers. The (anti-)TRβ and TTR binding activity were measured using (anti-)TRβ-CALUX and TTR-TRβ-CALUX bioassays. Anti-TRβ activity was found at eight sites, and TTR binding activity co-occurred there at six of these sites. The co-occurrence of TRβ-mediated antagonistic activity and TTR binding indicate that they may have common effect drivers. No sample exhibited TRβ agonistic activity. The extract from the site Bílina River, the most burdened with anti-TRβ activity, was further successfully fractionated, and this activity was revealed in the fraction, where mid-polar compounds prevailed. However, the suspect LC-HRMS analysis did not reveal the chemical effect drivers. Our results showed that anti-TRβ activity can be found in surface waters by employing passive sampling and frequently co-occurs with TTR binding activity. Overall, the fractionation procedure and non-target data acquisition used in this study can serve as a basis for searching the effect drivers in future research.
Keywords: Rivers; Czech Republic; Environmental Monitoring; Receptors, Thyroid Hormone; hmotnostní spektrometrie; Chromatography, Liquid; prealbumin; monitorování životního prostředí; Concentration addition; Thyroid hormone; Fractionation; chemické látky znečišťující vodu; Česká republika; řeky; Mass Spectrometry; receptory thyreoidních hormonů; Water Pollutants, Chemical; chromatografie kapalinová; Effect-directed analysis; Prealbumin; Transporter protein